An Adult Patient with Systemic Mastocytosis and B-Acute Lymphoblastic Leukemia - Theodoros Iliakis; Niki Rougkala; Panagiotis T. Diamantopoulos; Vasiliki Papadopoulou; Fani Kalala; Konstantinos Zervakis; Nefeli Giannakopoulou; Polixeni Chatzinikolaou; Georgia Levidou; Eleftheria Lakiotaki; Penelope Korkolopoulou; Efstratios Patsouris; et al. (Case Reports in Medicine)
Mastocytosis is a myeloproliferative neoplasm characterized by clonal expansion of abnormal mast cells, ranging from the cutaneous forms of the disease to mast cell leukemia. In a significant proportion of patients, systemic mastocytosis (SM) coexists with another hematologic malignancy, termed systemic mastocytosis with an associated hematologic nonmast cell lineage disorder (SM-AHNMD). Despite the pronounced predominance of concomitant myeloid neoplasms, the much more unusual coexistence of lymphoproliferative diseases has also been reported. Imatinib mesylate (IM) has a role in the treatment of SM in the absence of the KITD816V mutation. In the setting of SM-AHNMD, eradicating the nonmast cell malignant clone greatly affects prognosis. We report a case of an adult patient with SM associated with B-lineage acute lymphoblastic leukemia (B-ALL). Three cases of concurrent adult ALL and mastocytosis have been reported in the literature, one concerning SM and two concerning cutaneous mastocytosis (CM), as well as six cases of concomitant CM and ALL in children.